1994
DOI: 10.1177/0310057x9402200203
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron 4 mg for the Prevention of Nausea and Vomiting after Minor Laparoscopic Gynaecological Surgery

Abstract: We studied the efficacy and safety of intravenous ondansetron 4 mg for the prevention of postoperative nausea and vomiting after minor gynaecological laparoscopic surgery in Oriental women. This double-blind randomised study compared ondansetron with placebo, given before the induction of anaesthesia. The anaesthetic technique used thiopentone, fentanyl, atracurium, nitrous oxide and isoflurane. Patients were studied for 24 h with nausea assessed using a verbal numeric scale from 0-10 and emetic episodes recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…Ondansetron was the most effective drug in preventing postoperative nausea (4.55%) and vomiting (5.26%), which is in line with other authors 8-10, [13][14][15] . From all drugs studied, droperidol was the closest to ondansetron in preventing nausea (5.27%) and vomiting (9.09%) after videolaparoscopic gynecological procedures, in the conditions of this study.…”
Section: Discussionsupporting
confidence: 89%
“…Ondansetron was the most effective drug in preventing postoperative nausea (4.55%) and vomiting (5.26%), which is in line with other authors 8-10, [13][14][15] . From all drugs studied, droperidol was the closest to ondansetron in preventing nausea (5.27%) and vomiting (9.09%) after videolaparoscopic gynecological procedures, in the conditions of this study.…”
Section: Discussionsupporting
confidence: 89%
“…In a multicenter study, Kovac et al [3] reported that, in patients who failed prophylaxis with ondansetron 4 mg, a repeat dose of ondansetron 4 mg was no better than placebo for the treatment of established PONV. Although 2 other studies attempted to investigate redosing the agent used for prophylaxis for the treatment of PONV as part of a PONV prophylaxis study, the number of patients who experienced PONV was very small (b10) and, therefore, no meaningful conclusions could be drawn [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The meta‐analysis included 1247 patients in the ondansetron group and 875 patients in the placebo group (173 of these patients pertaining to two studies [21, 41] had been used simultaneously to compare the different doses of ondansetron). Four of the studies [18, 21, 46, 56], involving 698 patients treated with ondansetron and 524 with placebo were sponsored by the manufacturer.…”
Section: Resultsmentioning
confidence: 99%